Influence of emergent vegetation on sediment yield at cross-shore coastal environments - Turker, Umut; Yagci, Oral; Riazi, Amin; Kabdasli, Sedat (Coastal Engineering Research Council, 2017)
This study aimed to conceptually analyze the change in the magnitude of offshore sediment yield, wave energy, and offshore dislocation of sediment particles on coastal regions in the presence of coastal vegetation. This was achieved by comparing the simultaneous physical changes at coastal zones that were partly covered with vegetation while the remaining part had no vegetation. Series of experiments were conducted, and the interactions between the vegetation parameter, ratio of sediment yields, and offshore sediment dislocation distances were analyzed and determined to define the relationship between the parameters. The resultant empirical equations mostly followed a power relationship and fit the experimental data. The energy decay coefficient, reflecting the energy used in the presence of the vegetation, had strong protection ability and approached 80% energy decay as the vegetation parameter increased. The performance of natural vegetation cover was adequate, simulating a 50–80% decrease in offshore sediment yield, depending on the magnitude of the vegetation parameter.